Stabilization/solidification and recycling of sediment from Taihu Lake in China: Engineering behavior and environmental impact. (October 2020) - Tang, Pan-Pan; Zhang, Wan-Lu; Chen, Yong-Hui; Chen, Geng; Xu, Jie
Highlights: Reusing as fill material in an aquatic condition is a practicable management. Extra curing after sampling offers marked technical advantages as fill material. Leaching of S/S sediment has strong pH-dependence and slight time-dependence. Abstract: Investigations of stabilized/solidified sediment (S/S sediment) by simulated field-construction processes (crushing and filling) are fundamental to evaluating the potential reuse as fill materials. A series of tests were conducted on the samples prepared from S/S sediment grains (SG), which was obtained by crushing the cement treated sediment. By sampling the SG with different field-curing durations (t1: 28, 35, 56 and 98 days) and measuring them by unconfined compressive strength (UCS) tests, the effect of t1 on the UCS was investigated. By continually curing the samples prepared from the SG with 28 field-curing days in laboratory for an additional 7, 28, 35 and 70 days (t2) and subjecting them to UCS and tank leaching tests with different ambient (leachate) pH values (1, 4, 7, 10 and 14), the effect of t2 and ambient pH was evaluated. Increasing t1 and t2 was found to significantly influence the strength of SG, which highlights the importance of an appropriate curing period. The releases of the metals (As, Cr, Cu, Zn, Pb, Ni, and Hg) in the SG exhibited a strongly pH-dependence but less correlation with t2. Neutral conditions (pH = 7) offered the best immobilization capacity for Cu; As, Cr, Ni and Zn exhibited the lowest release at pH = 10; the release of Pb decreased moderately with increasing pH. The S/S sediment complied with the acceptance criteria in terms of metal release and can be regarded as an environmentally friendly fill material. The results highlight the technical feasibility of stabilized sediment recycling in aquatic environment projects.